The interrelation of the native species with cultural cerrado landscapes according local populations, of the municipality of Mirabela. - Maria Soares Silva, Amanda (Revista Desenvolvimento Social, 2020)
This paper seeks to understand the interrelation of the native species with cultural cerrado landscapes according local populations, of the municipality of Mirabela. The peculiarities of each territory is manifested in the culture of local populations in the popular knowledge, dialogue and appreciation with the nature, and also in mutual relations based on collectivity. Thus, this study considers the question: local populations, of the municipality of Mirabela, still maintain a differentiated and specialized interrelation with the cultural landscapes of the Cerrado, as the knowledge of medicinal plants? To answer the same evaluate imperative to expand the discussion, initially, for a description of the cerrado, highlighting its distribution and its potential in the flora. It was later made a binding on local populations and, subsequently, a description / analysis of landscapes naturais- board, slap and land culture exhibiting in each of the diversity of known native species and its possibilities of use.